Secondary hemophagocytic lymphohistiocytosis triggered by peripheral T‐cell lymphoma: An unusual case report - Yuxuan Che; Liye Xu; Xian Zhang; Xun Qiu; Jincheng Song; Xiaolei Ding; Xiuhua Sun (Clinical Case Reports, 2022)
Abstract Hemophagocytic lymphohistiocytosis (HLH) is a severe syndrome of pathological immune activation caused by activated macrophages and cytotoxic T cells. We report a 65‐year‐old male Chinese patient with typical HLH features caused by peripheral T‐cell lymphoma and then received chemotherapy. However, though the patient's symptoms and signs improved much, his liver function, especially bilirubin, worsened which could be caused by overwhelming cytokines production. Therefore, plasmapheresis was conducted two times and then his liver function significantly recovered. The patient got temporary remission and good quality of life for nearly 2 months but died because of disease progression. In conclusion, as HLH is associated with multiorgan failure, high rates of morbidity and mortality, there are three points to be mentioned. First, it is critical that HLH should be screened as early as possible and initiate effective therapies. Second, plasmapheresis could be a useful method to eliminate excess cytokines production and improve liver function. Third, organs support and nutrient supply are also necessary and important.